"He texts, she texts" gendered conversational styles in Philippine text messaging - Rojo-Laurilla, Mildred A. (2002)
The exploratory study aimed to examine whether characteristics of face-to-face (FTF) gendered interaction, as well as computer mediated communication (CMC), are evident in a new mediated communication situation, the cellular phone-mediated or "texted form" using the short messaging service(SMS) of today's most popular mobile phone units in addition, it attempted to describe the characteristics of this new form of mediated communication vis-a-vis its gendered context. Results of the study indicate that gendered texting conversational style, as opposed to FTF and CMC, is characterized by the following: a) equal footing between interlocutors, and b) equal use of linguistic strategies such as the use of questions as conversational opening and' cge/k' as second most preferred exit maker. Likewise, there are no clear-cut gendered language styles preferred by women and/or men in texting unlike western women's language style (in FTF) that was thought to be super-polite, overly grammatically correct, excessively using tag questions, expressing uncertainly, etc. Other characteristics include equal choice of language and language form (abbreviations and informal words similar to "spoken"language), preference for impersonal topics over personal ones, and use of emoticons as indicators of involvement. The data suggest that Filipino men and women are more or less similar in their "gendered texting conversational styles."
Includes bibliographical references (pages 85-86).